معطيات الاعلام الامريكي الموجه ازاء التدخلات العسكرية التركية في اقليم كوردستان العراق - الله, ابراهيم سعيد فتح (Sulaimani Journal for Humanities, 2021)
This study aims to identify the media vision of Alhurra channel, as an American media directed at Turkish military interventions in Kurdistan Region of Iraq. Content analysis method is used to analysis the media contents of Alhurra website that covered the Turkish interventions in Kurdistan Region of Iraq. The study reached a set of conclusions including that the Alhurra channel sought to form a pattern of insights towards the Turkish interventions by selectively highlighting internal, regional, and international positions on the interventions and marginalizing other positions. Based on the findings, the study recommends the necessity of working to display the humanitarian side of the Turkish intervention, especially suffering and losses of civilians in the region.